2012
DOI: 10.17761/ijyt.22.1.y47k2658674t1212
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Well-Being, Health Behaviors, and Weight Loss Among Participants in a Residential, Kripalu Yoga-Based Weight Loss Program

Abstract: The increasing prevalence of overweight and obesity in humans is a growing public health concern in the United States. Concomitants include poor health behaviors and reduced psychological well-being. Preliminary evidence suggests yoga and treatment paradigms incorporating mindfulness, self-compassion (SC), acceptance, non-dieting, and intuitive eating may improve these ancillary correlates, which may promote long-term weight loss. Methods: We explored the impact of a 5-day residential weight loss program, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 74 publications
2
40
0
Order By: Relevance
“…The effect size (Cohen's d = 0•61) attained in our study was comparable to previous short-term (e.g. 5 d) (18,47,48) or online selfguided self-compassion interventions (17,48) . These effect sizes are smaller than those reported in interventions with a longer period (i.e.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The effect size (Cohen's d = 0•61) attained in our study was comparable to previous short-term (e.g. 5 d) (18,47,48) or online selfguided self-compassion interventions (17,48) . These effect sizes are smaller than those reported in interventions with a longer period (i.e.…”
Section: Discussionsupporting
confidence: 86%
“…Our findings are consistent with the few other studies that have examined the efficacy of self-compassion on dietary intake. Those studies have also reported improvements in some aspects of the diet, such as increased scores on nutrition subscale of a health questionnaire (47) , and reduced frequency of dietary fat consumption (16) .…”
Section: Flexibility and Varietymentioning
confidence: 97%
“…Results from other yoga interventions have indicated that yoga increases physical activity and improves diet. 19,51 It is unclear why we did not observe improvements in exercise and diet. However, the current intervention was delivered over 3 days with the option to commute, compared to the previously published study, which was delivered as a residential program over 5 days with all participants staying as guests.…”
Section: Discussionmentioning
confidence: 85%
“…Perhaps simply asking someone about their desires/wants to move can instigate motivation states for movement. In populations suffering from addiction or stress, mindfulness meditation has been used to help individuals sense desires and then "ride the wave, " interpreting appetitive stimuli as "mere mental events" as a method to cope with dysfunctional urges (Braun et al, 2012;Papies et al, , 2020Jastreboff et al, 2018). In line with these advances, perhaps a method, such as mindfulness and/or vivid imagery, could be developed or modified to promote greater movement (Kavanagh et al, 2005).…”
Section: Practical Implicationsmentioning
confidence: 99%